Circular Polarization Millimeter-Wave SAR Imaging using 3D-Printed Helix Antennas - Ullmann, Ingrid; Root, Konstantin; Lomakin, Konstantin; Gold, Gerald; Gottinger, Michael; Helmreich, Klaus; Vossiek, Martin (SPIE Security + Defense Forum, 2020)
We propose the use of 3D-printed helix antennas for millimeter-wave radar imaging. This concept is promising for a number of reasons: Additive manufacturing involving 3D-printing is a relatively cost efficient fabrication technique and offers increased geometrical freedom of design compared to conventional manufacturing processes. From an imaging point of view, using helix antennas is advantageous because of the circular polarization the antennas emit. That way, imaging thin dipole-like structures is possible regardless of their orientation. In contrast, imaging systems using linearly polarized antennas are unable to image dipoles orientated orthogonally to their polarization direction. Radar systems using circular polarization additionally enable polarimetric imaging and decomposition. In security screening this can achieve a higher classification accuracy in discriminating threat objects and reduce false alarms. Furthermore, the thin helix antennas (typical coil diameter: ca. 1.5 mm) can be mounted very closely to each other, which is interesting for array design. A security screening example was investigated for demonstration: A cardboard box with metallic and dielectric threat objects was screened at 70 GHz – 90 GHz by a quasi-monostatic synthetic aperture radar consisting of two 3D-printed helix antennas, one right-hand and one left-hand circularly polarized. As a reference, the same object was screened with split-block linearly polarized horn antennas. With the proposed setup, the resolution of the reconstruction images was comparable to that of the reference system. However, the circular polarization was able to depict thin structures in a better fashion than the linearly polarized reference system.